‘Abdurra’uf Fitrat in Istanbul - Abdirashidov, Zaynabidin (De Gruyter, 2023)
Based on ‘Abdurra’uf Fitrat’s early publications the book discusses what intellectual milieu it was that shaped his worldview in the early 1910s, a worldview that could be designated as a first attempt at “freedom and sovereignty through Islam”. A thorough review of these publications also brings greater clarity how he related to the worldwide community of Muslims and how he positioned himself towards political unity of the Muslim World.